2015
DOI: 10.1161/hypertensionaha.114.03316
|View full text |Cite
|
Sign up to set email alerts
|

Distensibility of the Aorta and Carotid Artery and Left Ventricular Mass From Childhood to Early Adulthood

Abstract: Abstract-In adults, arterial distensibility decreases with age and relates to changes in cardiac left ventricular mass.Longitudinal data on changes in arterial distensibility from childhood to adulthood are lacking. Our aim was to study the effect of age and sex, and low-saturated fat dietary counseling on arterial distensibility from childhood to early adulthood. In addition, we assessed the association of arterial distensibility with left ventricular mass. Distensibility of the abdominal aorta and common car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…33 To compensate lack of central BP measurement, we previously determined cdist and adist using also estimated central pulse pressures. 7 When these distensibility measures were used, the results on the association of age and sex with distensibility remained similar to those when brachial BP was used, suggesting that the use of brachial data is applicable. 7 Furthermore, previous studies have shown an excellent correlation between invasively measured BPs from ascending aorta and noninvasively measured BPs from brachial artery, supporting the use of brachial artery pulse pressure to derive cdist and adist.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…33 To compensate lack of central BP measurement, we previously determined cdist and adist using also estimated central pulse pressures. 7 When these distensibility measures were used, the results on the association of age and sex with distensibility remained similar to those when brachial BP was used, suggesting that the use of brachial data is applicable. 7 Furthermore, previous studies have shown an excellent correlation between invasively measured BPs from ascending aorta and noninvasively measured BPs from brachial artery, supporting the use of brachial artery pulse pressure to derive cdist and adist.…”
Section: Discussionmentioning
confidence: 63%
“…7 When these distensibility measures were used, the results on the association of age and sex with distensibility remained similar to those when brachial BP was used, suggesting that the use of brachial data is applicable. 7 Furthermore, previous studies have shown an excellent correlation between invasively measured BPs from ascending aorta and noninvasively measured BPs from brachial artery, supporting the use of brachial artery pulse pressure to derive cdist and adist. 42,43 We and others have reported that the correlations between repeated distensibility measures are relatively weak.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations